Frequency Adjustment in Solar Systems: How to Check and Determine the Location of Solar Panels - Sabzalian , M (Elsevier, 2024)
This chapter will discuss the location and factors involved in determining the proper size and characteristics of solar energy. This chapter aims to use the geographic information system to find the best locations for constructing solar power plants in different Iranian provinces. The earth does not store the sun’s total irradiance energy, which is either consumed for sustaining living organisms or transferred outside of the earth’s surface through various mechanisms such as evaporation, sensible heat, and reflection. Since the received energy should be used to produce electricity at the moment, it is very important to find a site with optimum efficiency. With its suitable location in terms of geostationary orbits, Iran is well-positioned to receive solar irradiance. Therefore compared to many European countries, it has a great capacity to receive and use solar energy, which will be further examined in the following sections. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.